Association between Monocyte-to-Lymphocyte Ratio and Inflammation in Chronic Kidney Disease: A Cross-Sectional Study - Qin Zhou; Xiaofei Shao; Li Xu; Hequn Zou; Wenli Chen (Kidney & Blood Pressure Research)
Introduction: Inflammation plays a key role in chronic kidney disease (CKD). Monocyte-to-lymphocyte ratio (MLR) is a novel inflammatory marker. The purpose of this study was to evaluate the relationship between MLR and inflammation in CKD patients. Methods: In total, 1,809 subjects were recruited from Wanzhai Town, Zhuhai City, between December 2017 and March 2018 for a cross-sectional survey. Patients were categorized based on the absence (hypersensitive C-reactive protein [hsCRP] level ≦3 mg/L) or presence (hsCRP level >3 mg/L) of inflammation. Logistic regression models and MLR quartiles were used to explore the relationship between MLR and inflammation in CKD patients. Results: Among 1,809 subjects, 403 (22.2%) had CKD. Significant differences in systolic blood pressure, estimated glomerular filtration rate, white blood cell (WBC), neutrophil, monocyte, MLR, and interleukin-6 (IL-6) levels were observed between noninflammatory group and inflammatory group. The highest MLR quartile had higher Scr, WBC, neutrophil, monocyte, IL-6, and hsCRP values and lower eGFR and lymphocyte values. Comparing the lowest quartile of MLR, the OR (95% CI) of inflammation risk in the highest quartile was 2.30 (1.24–4.27) after adjustment for confounding factors. The area under the curve of MLR for predicting inflammation was 0.631. The cutoff point for the MLR was 0.153. Conclusion: A high MLR was significantly and independently associated with inflammation in patients with CKD, making MLR a potential marker for inflammation in this demographic. MLR may also predict the severity of CKD.